THE EFFECT OF TUI NA MASSAGE THERAPY TOWARDS EATING BEHAVIOR IN THE DEVELOPMENT AREAS OF THE SALT HEALTH CENTER OF DEPOK CITY YEAR 2022 - Syamsiah, Siti; Febry Mutiariami Dahlan; Siti Nur Inayah (Sean Institute, 2022)
Background: Toddler age is a period that plays an important role in the process of growth and development of a person and is strongly influenced by the eating behavior of toddlers. One of the efforts that can be done to improve and change the eating behavior of toddlers is by doing Tui Na massage. Purpose: the purpose of this study is to find out how the effect of Tui Na massage on the eating behavior of toddlers in the assisted areas of the Pengasinan Health Center in Depok City in 2022 Methodology: This type of research is a quasi-experimental design with a pre and post-test design with a control group. The population in this study were all toddlers aged 3-5 years in the assisted areas of the Pengasinan City Health Center in Depok as many as 1,054 toddlers divided into 18 posyandu with a total sample of 30 people. The sampling technique is Cluster Random Sampling. The research was conducted in the target area of ​​the Pengasinan Health Center in Depok City from April to July 2022. The data used are primary data. Data were analyzed by univariate and bivariate with paired and independent t test. The data is processed using a computer with the SPSS program. Results: The results showed that there was an effect of Tui Na massage therapy on the eating behavior of toddlers in the intervention group (p value 0.001) and there was no effect on examinations 1 and 2 on the eating behavior of toddlers in the control group (p value 0.233) and there were differences between the control group and the intervention group on the eating behavior of toddlers (p value 0.000). Conclusion: The conclusion that Tui Na massage has a good influence on toddlers' eating behavior Suggestion: It is hoped that this Tui Na massage can be applied to improve eating behavior in toddlers